2015
DOI: 10.1590/1678-457x.6564
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and sensory properties of gluten-free kibbeh formulated with millet flour (Pennisetum glaucum (L.) R. Br.)

Abstract: Pearl millet flour was utilized in kibbeh formulations instead of whole-wheat flour. Physicochemical properties, oxidation stability and sensorial characteristics of control kibbeh made with whole-wheat flour (CT) were compared with kibbehs prepared with millet flour (roasted or wet) and stored for 90 days (-18 °C). Kibbeh prepared with millet flour presented good oxidation stability (TBARS concentration). Baked kibbehs (with roasted millet flour) presented good acceptability and kibbeh samples did not differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Kobbah was made as described by Brazil et al [ 37 ], soaking ground bulgur flour into hot water (80 °C) for 1 h, then the wheat flour, oil, salt and spices were added and mixed with the soaked ground bulgur. The dough was kept at the refrigerator for 1 h. Stuffing: onions, salt and spices were mixed with minced beef meat then cooked with olive oil.…”
Section: Methodsmentioning
confidence: 99%
“…Kobbah was made as described by Brazil et al [ 37 ], soaking ground bulgur flour into hot water (80 °C) for 1 h, then the wheat flour, oil, salt and spices were added and mixed with the soaked ground bulgur. The dough was kept at the refrigerator for 1 h. Stuffing: onions, salt and spices were mixed with minced beef meat then cooked with olive oil.…”
Section: Methodsmentioning
confidence: 99%
“…Millets release less glucose over a longer duration of time as compared to wheat and rice. One of the most famous meat-based snack foods in Turkish cuisine, the “kibbeh,” was prepared using millet flour which, maintained nutritional value and sensorial quality as a gluten-free, cereal-based formulation because of its better oxidation stability measured using thiobarbituric acid-reactive substances (37). To date, the use of minor millets in gluten-free product formulation is limited and needs to be explored globally.…”
Section: Gluten-free Floursmentioning
confidence: 99%
“…It was concluded that 5% sorghum flour is optimum to prepare gluten-free nuggets in terms of sensory quality. Brasil et al (2015) Chicken nugget Pecans…”
Section: Chicken Nugget Rice Flourmentioning
confidence: 99%
“…Öztürk et al (2018) recommended that especially dietary fiber sources could supply to formulate gluten-free poultry products that have equivalent cooking characteristics to standard gluten-containing products, meanwhile improving health profile. Except for coated meat products, some non-glutinous flours have been also mentioned to improve nutritive, sensory and technological quality of different gluten-free meat products like fish patties (Romero et al, 2018) and kibbeh (Brasil et al, 2015).…”
Section: Jackson (2016)mentioning
confidence: 99%